2021
DOI: 10.1007/s10796-021-10181-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Organizational Users’ Intentions and Behavior to AI Integrated CRM Systems: a Meta-UTAUT Approach

Abstract: This paper tests the meta-analysis based unified theory of acceptance and use of technology (meta-UTAUT) model to predict the behavioral intentions of organizational users and their use behavior to artificial intelligence (AI) integrated customer relationship management (CRM) systems. Data was collected from 315 organizational users in India. The hypotheses draw on the theoretical underpinnings which have been statistically validated. Results show that CRM quality and satisfaction significantly influences an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
40
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 108 publications
9
40
2
1
Order By: Relevance
“…In operation management, the adoption of AI use was influenced by six factors, including social factors and facilitating conditions (Grover et al, 2020). Chatterjee et al (2021) evaluated the use of AI-integrated customer relation systems in Indian organizations, and their findings validated the models underpinning and other exogenous customer relationship management variables. Chatterjee and Bhattacharjee (2020) assessed the adoption of AI in higher education, where perceived risk, facilitating condition, and effort expectancy impact attitude, influencing the intention to use AI in higher education.…”
Section: Unified Theory Of Acceptance and Use Of Technologymentioning
confidence: 90%
See 3 more Smart Citations
“…In operation management, the adoption of AI use was influenced by six factors, including social factors and facilitating conditions (Grover et al, 2020). Chatterjee et al (2021) evaluated the use of AI-integrated customer relation systems in Indian organizations, and their findings validated the models underpinning and other exogenous customer relationship management variables. Chatterjee and Bhattacharjee (2020) assessed the adoption of AI in higher education, where perceived risk, facilitating condition, and effort expectancy impact attitude, influencing the intention to use AI in higher education.…”
Section: Unified Theory Of Acceptance and Use Of Technologymentioning
confidence: 90%
“…Cao et al (2021) found no significant association between performance expectancy and intention to use technology, but a positive influence was found on attitude toward AI in decision-making. Chatterjee et al (2021) found that performance expectancy was associated with using AI-enabled systems to enhance performance. Based on the above review, the following hypotheses were developed: H1: Performance expectancy will positively affect the use of AIenabled tools.…”
Section: Proposed Conceptual Model and Hypothesis Development Perform...mentioning
confidence: 99%
See 2 more Smart Citations
“…product adoption [41], customer relationship management [42], disaster relief operations [43] and retailing [44], among others. Venkatesh, et al [45] first proposed the theory by combining eight information systems adoption theories into a unified framework to investigate the motivations driving individuals to adopt information systems.…”
Section: A Unified Theory Of Acceptance and Use Of Technology (Utaut)mentioning
confidence: 99%